Appraisal of Thermal Comfort in Non-Air-conditioned and Air-conditioned Railway Pantry Car Kitchens - Alam, Md. Sarfaraz; Muthiah, Arunachalam; Ravindra Salve , Urmi (International Journal of Integrated Engineering, 2020)
This study details the consequences of a thermal comfort survey conducted in N-AC â€œNon-Airconditionedâ€ and AC â€œAirconditionedâ€ pantry car kitchens in Indian Railways. The research was carried out on 6 railway pantry car kitchens in which 29 chefs participated. Field measurement and subjective evaluation techniques performed in this study during the working period of chefs. The aim of the present research to compare N-AC and AC railway pantry car kitchen. While the objective of the study to determine the thermal comfort parameters â€œair temperature, mean radiant temperature, relative humidity and air velocityâ€ of both pantry car kitchens and examine the subjective responses; and to evaluate the thermal comfort of both pantry car kitchens using the PMV â€œPredicted Mean Voteâ€ and PPD â€œPredicted Percent Dissatisfiedâ€ indices and compare them with actual sensation votes. A result of this study revealed that all thermal comfort parameters do not comply with the recommended ASHRAE 55 Standard in both pantry car kitchens. There is no considerable difference between both pantry car kitchen based on the subjective assessment during the working period and all the chefs' votes were found to be outside the range of the ASHRAE 55 central three categories (-1, 0, +1) votes. Which indicates that the chefs are not satisfied with the current environment. While for N-AC pantry car, PMV and PPD value estimated were 3.10 and 99% respectively, with "hot" thermal sensation. Similarly, for AC pantry car, PMV and PPD value estimated were 2.21 and 85% respectively, with "warm" thermal sensation. The estimated values of PMV and PPD do not follow the ASHRAE-55 2017 and ISO 7730 standard. Therefore, PMV indices are not directly applicable for thermal comfort application in a pantry car kitchen environment due to high temperature. In both the pantry car kitchen, there is no difference between predicted and actual sensation votes. In further establish the other method and technique to identify the comfort temperature for better workmanship of chefs in a pantry car kitchen.